Wither the plurality of decolonising the curriculum? Safe spaces and identitarian politics in the arts and humanities classroom - Mendes, Ana Cristina (2022)
Contributing to the debate on decolonising the curriculum, this reflective article questions: What does a safe space in a decolonised classroom mean? For whom is it safe? And at what cost? Must we redraw the parameters of ‘safe’? Prompted by a real-life ‘n-word incident’ in the classroom, this article unpacks the collision of decolonising the curriculum to continue making teaching and learning more pluriversal and inclusive, with the enactment of the ‘wounded attachments’ of identitarian politics and the playing of ‘Privilege or Oppression Olympics’. Using snippets from British parody and satire on decolonising the university, we query how far wokeness in a university setting can become political correctness taken to extremes that threaten decolonising efforts. In its concluding reflections, the article makes tentative recommendations for setting up safe spaces, away from self-silencing or censoring, and backing away from contention and provocation in the classroom.